The impact of online and offline experiences on McDonald's customers' brand equity - Nurhad Nurhad; Gesit Thabrani (Universitas Negeri Padang, 2023)
This study aims to analyze the effect of online and offline experiences on brand equity among consumers in Padang City. The population in this study is comprised of consumers who have shopped directly at restaurants and through applications or websites. The number of samples in this study was 200. Data collection was carried out by distributing questionnaires online. Data processing is done using SmartPLS software. The results of this study indicate that (1) Offline Experience has a positive and significant effect on Brand equity; (2) Online Experience has a positive and significant effect on Brand equity; and (3) Offline Experience has a positive and significant effect on Online experience.